Evaluating the Potentials of the Housing Fund Law to Support Housing Finance Policies in Iraq - Alanizi, Arshad; Alsayed, Muna; Mahmood, Alyaa (Al-Nahrain Journal for Engineering Sciences, 2022)
After long eras of socialism, wars and economic embargo when Iraqi people were severely exhausted, Iraq finally adopts free market economy. Its Gross Domestic Product (GDP) increased rapidly.The fortune was to flow in a proper frame of legislations to Iraqis.Since wealth needs time to grow for a person, and housing commodity is of high costs, then legislation were to be issued to organize flow of the national wealth to support private sector in housing finance.In respond, the Law of Iraqi Housing Bank (IHB) No. 32 was issued in 2011.This research is to solve the conflicts of the (IHB) Law and to support Iraqi legislators regarding this aspect. This research claims that this law should be revised by the Iraq Parliament. The research comes to help in this mission. The law of (IHB) should not conflict with The Iraqi Constitution.The range of this research is the “Status-in-force” Iraqi legislations only.It discusses the housing finance relations in various Iraqi legislations.